2013
DOI: 10.1016/j.neurobiolaging.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in neuroactive steroid levels in 3xTg-AD mice

Abstract: Although neuroactive steroids exert neuroprotective actions in different experimental models of neurodegenerative diseases, including those of Alzheimer's disease (AD), their relationships with aged related physiological and pathological brain changes remain to be clarified. In this study the levels of pregnenolone, dehydroepiandrosterone, progesterone, dihydroprogesterone, tetrahydroprogesterone, isopregnanolone, testosterone, dihydrotestosterone, 5α-androstane-3α,17β-diol, 5α-androstane-3β,17β-diol, 17α-estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 51 publications
5
62
0
Order By: Relevance
“…This is in agreement with the general decrease of neuroactive steroid levels observed in different animal models of neurodegeneration, such as Parkinson's disease, multiple sclerosis, peripheral neuropathies and diabetic encephalopathy [31,171,[183][184][185][186][187][188][189][190][191][192][193].…”
Section: Effects Of 5α-ri Therapy On Neurobehavioral Functions and Nesupporting
confidence: 84%
See 2 more Smart Citations
“…This is in agreement with the general decrease of neuroactive steroid levels observed in different animal models of neurodegeneration, such as Parkinson's disease, multiple sclerosis, peripheral neuropathies and diabetic encephalopathy [31,171,[183][184][185][186][187][188][189][190][191][192][193].…”
Section: Effects Of 5α-ri Therapy On Neurobehavioral Functions and Nesupporting
confidence: 84%
“…Alteration in PROG metabolism has been also further confirmed in male brains from a mouse model of AD (i.e., 3xTg-AD mice) [186]. An age-related decrease in the levels of PROG, together with an increase in the levels of its metabolite 5α-DHP, was detected in the limbic region of wild type (WT) and 3xTg-AD mice.…”
Section: Effects Of 5α-ri Therapy On Neurobehavioral Functions and Nementioning
confidence: 71%
See 1 more Smart Citation
“…Studies performed in humans, animals, and cellular models have shown alterations in the synthesis of neurosteroids that declined during brain aging paralleled by a loss of important nervous functions, such as memory, and were further associated with PD and AD [14][15][16]. Thus, several neurosteroids have been quantified in various brain regions of aged AD patients and aged non-demented controls.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as demonstrated in experimental models and clinical studies, neurodegenerative and psychiatric disorders affect neuroactive steroid levels [13,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. For instance, neuroactive steroid levels are modified in experimental models of acquired peripheral neuropathy, such as those due to trauma [68] or diabetes [50,61] and inherited peripheral neuropathy (e.g., Charcot-Marie-Tooth type 1A, CMT1A) [49].…”
Section: Neural Pathology Influences Neuroactive Steroid Levelsmentioning
confidence: 99%